Age- and Hypertension-Related Changes in NOS/NO/sGC-Derived Vasoactive Control of Rat Thoracic Aortae. (9th March 2022) - Berenyiova, Andrea; Balis, Peter; Kluknavsky, Michal; Bernatova, Iveta; Cacanyiova, Sona; Puzserova, Angelika
Abstract : This study was aimed at examining the role of the NOS/NO/sGC signaling pathway in the vasoactive control of the thoracic aorta (TA) from the early to late ontogenetic stages (7 weeks, 20 weeks, and 52 weeks old) of normotensive Wistar-Kyoto (WKY) rats and spontaneously hypertensive rats (SHRs). Systolic blood pressure (SBP) and heart rate (HR) were significantly increased in SHRs compared to age-matched WKYs, which was associated with left heart ventricle hypertrophy in all age groups of rats. The plasma urea level was increased in 20-week-old and 52-week-old SHRs compared with WKYs without increasing creatinine and uric acid. The total cholesterol levels were lower in 20-week-old and 52-week-old SHRs than in WKYs, but triglycerides were higher in 7-week-old SHRs. The fructosamine level was increased in 52-week-old SHRs compared with age-matched WKYs and unchanged in other age groups. Superoxide production was increased only in 7-week-old SHRs compared to age-matched WKYs. The endothelium-dependent relaxation (EDR) of the TA deteriorated in both rat strains during aging; however, endothelial dysfunction already occurred in 20-week-old SHRs and was even more enhanced in 52-week-old rats. Our results also demonstrated increased activity of NOS in 52-week-old WKYs. Moreover, 7-week-old and 52-week-old WKY rats displayed an enhanced residual EDR after L-NMMA (NOS inhibitor) incubation compared with 20-week-old rats. Our results showed that in 7-week-old SHRs, the residual EDR after L-NMMA incubation was increased compared to that in other age groups. The activity of NOS in the TA was comparable in 7-week-old and 20-week-old SHRs, but it was reduced in 52-week-old SHRs compared to younger SHRs and 52-week-old WKYs. Thus, it seems that, in contrast to SHRs, the NOS/NO system in WKYs is probably able to respond to age-related pathologies to maintain endothelial functions and thus optimal BP levels even in later periods of life.